Vibration of pre-loaded structures - Soh, Bernard Woon Sen (Nanyang Technological University, 2021)
This Final Year Project (FYP) deals with the determination of the natural frequencies of pre-loaded structures using the Finite Element Analysis (FEA) software, ANSYS Mechanical APDL Version 2020 R2. Firstly, the natural frequencies of a cantilever beam with a square cross section are determined without pre-loading. The mesh density is varied, and the convergence of the natural frequencies with the mesh density has been studied. For subsequence analyses, an optimal mesh density is used. Next, the natural frequencies are determined considering different types of loads such as axial load, tip-shear load, uniformly-distributed load, and moment load. With the increasing tensile-axial load, the natural frequencies of the bending modes increase. With increasing compressive load, the natural frequencies of the bending modes decrease. With increasing tip-shear load and uniformly-distributed load, the natural frequencies of the bending modes decrease. There are no significant changes to the natural frequencies of the bending modes with increasing moment load. As for the natural frequencies of the longitudinal mode, there are no significant changes with varying loads. Secondly, the natural frequencies of a cantilever I-beam are determined with and without pre-loading. All the 4 types of loadings, viz., axial load, tip-shear load, uniformly-distributed load, and moment load, have been considered. Generally, the trend is somewhat similar to that of a cantilever beam with square cross section. Finally, the modal analysis of a pre-loaded truss bridge is carried out. The first natural frequency is computed for increasing load value. With increasing load, the natural frequency of the bending mode decreases.